FDA Approval Summary: Midostaurin for the Treatment of Advanced Systemic Mastocytosis. (16th August 2018) - Kasamon, Yvette L.; Ko, Chia‐Wen; Subramaniam, Sriram; Ma, Lian; Yang, Yuching; Nie, Lei; Shord, Stacy; Przepiorka, Donna; Farrell, Ann T.; McKee, Amy E.; Pazdur, Richard
Abstract: : In April 2017, the U.S. Food and Drug Administration granted regular approval to midostaurin for the treatment of adult patients with aggressive systemic mastocytosis (ASM), systemic mastocytosis with associated hematological neoplasm (SM‐AHN), or mast cell leukemia (MCL). Approval was based on results from CPKC412D2201, a single‐arm trial of midostaurin (100 mg orally twice daily) in previously treated or untreated patients. For the patients with ASM and SM‐AHN, efficacy was established on the basis of confirmed complete remission (CR) plus incomplete remission (ICR) by modified Valent criteria with six cycles of midostaurin. There were no CRs reported; ICR was achieved by 6 of 16 patients (38%; 95% confidence interval [CI]: 15%–65%) with ASM and by 9 of 57 patients (16%; 95% CI: 7%–28%) with SM‐AHN. Within the follow‐up period, the median duration of response was not reached for the patients with ASM (range, 12.1+ to 36.8+ months) or with SM‐AHN (range, 6.6+ to 52.1+ months). For the patients with MCL, efficacy was established on the basis of confirmed CR using modified 2013 International Working Group‐Myeloproliferative Neoplasms Research and Treatment‐European Competence Network on Mastocytosis criteria. Of 21 patients with MCL, 1 (5%) achieved a CR. Of 142 patients with SM evaluated for safety, 56% had dose modifications for toxicity, and 21% discontinued treatment due to a toxicity. Over 50% reported nausea, vomiting, or diarrhea, and ≥30% reported edema, musculoskeletal pain, fatigue, abdominal pain, or upper respiratory tract infection. New or worsening grade ≥3 lymphopenia, anemia, thrombocytopenia, or neutropenia developed in ≥20%. Although midostaurin is an active drug for treatment of advanced SM, it is not clear that the optimal dose has been identified. Implications for Practice: Midostaurin is the only U.S. Food and Drug Administration‐approved therapy for patients with systemic mastocytosis with associated hematological neoplasm and mast cell leukemia and is the only therapy approved for patients with aggressive systemic mastocytosis regardless of KIT D816V mutation status. Based on response rate and duration, midostaurin has meaningful clinical activity in these rare, life‐threatening diseases. Abstract : In April 2017, the U.S. Food and Drug Administration (FDA) granted regular approval to midostaurin for the treatment of adult patients with aggressive systemic mastocytosis, systemic mastocytosis with associated hematological neoplasm, and mast cell leukemia. This article summarizes the FDA clinical review and rationale for the approval.